Spatiotemporal Regulation of the Bone Immune Microenvironment via Dam‐Like Biphasic Bionic Periosteum for Bone Regeneration (Adv. Healthcare Mater. 1/2023). Issue 1 (2nd January 2023) - Xu, Zonghan; Wu, Liang; Tang, Yu; Xi, Kun; Tang, Jincheng; Xu, Yichang; Xu, Jingzhi; Lu, Jian; Guo, Kaijin; Gu, Yong; Chen, Liang
Abstract : Bone Regeneration A hybridized biphasic bionic periosteum which acts as a "dam" to control the release of IL‐4 is presented in article 2201661 by Jian Lu, Kaijin Guo, Yong Gu, Liang Chen, and co‐workers, constructing a coordinated bone immune microenvironment for vascular maturation and osteogenesis, so as to break through the predicament of the contradiction between immune response and bone tissue regeneration.